Effect of girdling on nutrition and rooting of cuttings of the apple rootstock 'Malling-Merton 106' - Fachinello, José Carlos; Lucchesi, Antonio Augusto; Gutierrez, Luiz Eduardo (Pesquisa Agropecuaria Brasileira, 2014)
Mother plants of 'Malling-Merton 106' rootstock were subjected to three types of girdling (girdled, stranguled and nongirdled) in two periods before harvest of cuttings for rooting. Fifty percent of the cuttings were treated with an IAB (indolebutyric acid) treatment and fifty percent were used to determine total soluble sugar and nitrogen. One hundred and two days later cuttings were evaluated in the rootbed. Results showed that girdling stimulated rooting of cuttings as well as quantity of dry matter of roots and branches, especially in cuttings from the basal portions. Girdled cuttings do not require application of growth regulators for root initiation. There were greater dry matter gains in the treatments in which indolebutyric acid was applied. There was no correlation between soluble sugar content and total nitrogen and increased rooting of cuttings.
Keywords: mother plant; indolebutyric acid; nitrogen